The benefit of microscopic measuring techniques for unveiling structure-mobility relations in molecular diffusion under confinement - Kärger, Jörg (Diffusion Fundamentals, 2005)
Molecular propagation under confinement reveals a multitude of peculiarities in comparison with diffusion in the bulk phase of a fluid. The present review is based on the experimental evidence of microscopic measuring techniques on tracing such phenomena. A short introduction into the fundamentals, main applications and limitations of pulsed field gradient NMR as the probably most versatile technique for in-situ diffusion measurements in complex systems shall be given. The information provided by this technique is complemented by investigations using interference and IR microscopy. Confinement is considered to occur by both host–guest interactions and the formation of internal boundaries. In several cases the experimental studies are shown to give rise to quite general theoretical considerations, just like – vice versa– there is a multitude of theoretical predictions waiting for their experimental confirmation.